Penegakan Sanksi Hukum terhadap Penipuan di E-Commerce Shopee Sebagai Upaya Perlindungan Konsumen : Studi Kasus di Wilayah Polres Cirebon Kota - Hadi Alfian Ilham; Dadan Taufik Fathurohman (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze law enforcement against perpetrators of fraudulent practices on the Shopee e-commerce platform within the jurisdiction of the Cirebon City Police and examine how the perpetrators are legally responsible for consumer losses incurred due to these fraudulent practices. The research method used is an empirical juridical method with a sociological approach through a case study in the Cirebon City Police area. The results of the study indicate that findings related to the law enforcement process by the Cirebon City Police are hampered, especially in terms of evidence, the use of electronic evidence and the application of provisions in the ITE Law and the Consumer Protection Law. In addition, law enforcement against e-commerce fraudulent practices requires synergy between law enforcement officials, consumer protection agencies, business actors and digital platforms to realize effective legal protection.